Efficient algorithms for frequent pattern mining in many-task computing environments - Lin, Kawuu W.; Lo, Yu-Chin (Knowledge-based systems, 2013)
The goal of data mining is to discover hidden useful information in large databases. Mining frequent patterns from transaction databases is an important problem in data mining. As the database size increases, the computation time and required memory also increase. Because the number of items increases, the user behaviours also become more complex. To solve the problem of increasing complexity, many researchers have applied parallel and distributed computing techniques to the discovery of frequent patterns from large amounts of data. However, most studies have focused on improving the performance for a single task and have neglected the many-task computing issue, which is important in the current cloud-computing environments. In these environments, an application is often provided as a service, e.g., the Google search engine, implying that many users can use it simultaneously. In this paper, we propose a set of algorithms, containing the Equal Working Set (EWS) algorithm, the Request On Demand (ROD) algorithm, the Small Size Working Set (SSWS) algorithm and the Progressive Size Working Set (PSWS) algorithm, for frequent pattern mining that provides a fast and scalable mining service in many-task computing environments. Through empirical evaluations in various simulation conditions, the proposed algorithms are shown to deliver excellent performance with respect to scalability and execution time.